Analysis of the String Structure Near Break-up of A Slender Jet of An Upper Convected Maxwell Liquid - A. Y. Gunawan; W. S. Budhi (Journal of Mathematical and Fundamental Sciences, 2009)
In this paper, we analytically study the string structure near the break-up of a slender jet of a viscoelastic liquid surrounded by air. The governing equations are derived from the conservation laws of mass and momentum, and the rheological equation of the jet. The rheological equation of the jet is assumed to satisfy an Upper Convected Maxwell (UCM) model. Introducing a stretch variable and then applying a transformation, we obtain a coupled system of nonlinear differential equations. Via these equations, we then show that the UCM jet does not break up in finite time, which physically means that it has sufficient time to exhibit the string structure before it breaks up due to the dominant surface force.